Hubungan Motivasi Belajar Siswa dengan Efektivitas Pembelajaran PJOK di SMP Negeri Nganjuk (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The study aims to examine the relationship between students’ learning motivation and the effectiveness of PE learning at SMP Negeri 7 Nganjuk. Learning motivation is viewed as an important psychological factor that encourages students’ engagement, persistence, and sustained participation in the PJOK learning process. This study employed a quantitative approach with a correlational design. The research population consisted of 857 students of SMP Negeri 7 Nganjuk, with a sample of 92 students determined through accidental sampling techniques. The research instruments were questionnaires measuring learning motivation and PE learning effectiveness, which were adapted from previous studies and had been confirmed to be valid and reliable. Data analysis was conducted using descriptive and inferential statistics with the Spearman Rank Correlation test, as one of the variables was not normally distributed. The results indicate a positive and significant correlation between students’ learning motivation and the effectiveness of PE learning, with a correlation coefficient of 0.432 and a significance value of 0.00. These findings suggest that increases in students’ learning motivation are accompanied by improvements in the effectiveness of PJOK learning. The results emphasize the importance of developing instructional strategies that enhance learning motivation to support the effectiveness of PE learning at the junior high school level.